2013
DOI: 10.1111/gfs.12088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing management on herbage protein concentration, milk production and nitrogen excretion of dairy cows in mid‐lactation

Abstract: The objective of this experiment was to use diurnal and temporal changes in herbage composition to create two pasture diets with contrasting ratios of water‐soluble carbohydrate (WSC) and crude protein (CP) and compare milk production and nitrogen‐use efficiency (NUE) of dairy cows. A grazing experiment using thirty‐six mid‐lactation Friesian x Jersey cows was conducted in late spring in Canterbury, New Zealand. Cows were offered mixed perennial ryegrass and white clover pastures either in the morning after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
15
1
1
Order By: Relevance
“…In grazed pasture systems, pasture crude protein levels are often well in excess of animal crude protein requirements, leading to higher urinary N concentrations (Litherland & Lambert 2007). Work by Miller et al (2012) reported daily N excretion rates from cows grazing kale to be notably lower than those grazing pasture (Pacheco et al 2010;Bryant et al 2013). Further work on determining urinary N concentrations from dairy cows grazing winter forage crops is required to better understand typical N loading rates of cow urine deposits in grazed winter forage crop systems to avoid an over-estimation or under-estimation of paddockscale leaching losses.…”
Section: Discussionmentioning
confidence: 99%
“…In grazed pasture systems, pasture crude protein levels are often well in excess of animal crude protein requirements, leading to higher urinary N concentrations (Litherland & Lambert 2007). Work by Miller et al (2012) reported daily N excretion rates from cows grazing kale to be notably lower than those grazing pasture (Pacheco et al 2010;Bryant et al 2013). Further work on determining urinary N concentrations from dairy cows grazing winter forage crops is required to better understand typical N loading rates of cow urine deposits in grazed winter forage crop systems to avoid an over-estimation or under-estimation of paddockscale leaching losses.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies where significant effects of HM on the productive performance of cows were observed [8,18,27], it is feasible to observe that, when comparing high and low HM, the differences between treatments in the pre-grazing ADF content are in the range of 40 to 60 g/kg, values higher than those observed in our study. The HHM treatment was generated by delaying the regrowth period before the start of the study in relation to the regrowth period of MHM (+15 days of regrowth), which may influence fiber concentration in the pasture and, consequently, its digestibility [2,28]. However, the higher content of pre-grazing ADF and during the first 120 min of the first GS in HHM did not affect the concentration of DOMD, as fiber digestibility in a vegetative leafy spring pasture is high (>800 g/kg) and therefore an increase in ADF does not necessarily result in lower DOMD [29].…”
Section: Nutritive Value Of the Pasture During The Grazing Down Procementioning
confidence: 99%
“…Urine N concentration also varies with animal reproductive status, season, and time of day Betteridge et al, 1986;Hoogendoorn et al, 2010;Bryant et al, 2013). Methods for estimating urine N concentration are "spot" sampling (Hoogendoorn et al, 2010), urine sensors (Betteridge et al, 2010b), and modeling based on intake of N; sodium and potassium (Bannink et al, 1999).…”
Section: The Urine Patch In Grazed Pasture Systems 21 Urine Compositionmentioning
confidence: 99%
“…Methods for estimating urine N concentration are "spot" sampling (Hoogendoorn et al, 2010), urine sensors (Betteridge et al, 2010b), and modeling based on intake of N; sodium and potassium (Bannink et al, 1999). Bryant et al (2013) recognized the need for caution when interpreting urine N concentration from spot sampling, Table 1 Characteristics of urine patches deposited by dairy and beef cattle, sheep, and deer grazing predominantly pasture-based diets. Of the range of studies reported in Haynes and Williams (1993b) Clark et al…”
Section: The Urine Patch In Grazed Pasture Systems 21 Urine Compositionmentioning
confidence: 99%
See 1 more Smart Citation